STRENGTHENING GLOBAL AIRWORTHINESS OVERSIGHT: AN INDONESIAN PERSPECTIVE ON ICAO STANDARDS AND CERTIFICATION ACCOUNTABILITY - Ayu Nrangwesti; Amriyati; Wildani Angkasari (KANUN:JURNAL ILMU HUKUM, 2025)
Airworthiness is a foundational element of civil aviation safety. Fatal accidents from 2018 to 2025 reveal weaknesses in supervision and negligence within the aircraft certification process. This article analyzes how airworthiness regulation and oversight failures across regulators, operators, manufacturers, and certification bodies, affect safety and accountability, including the adequacy of the International Civil Aviation Organization (ICAO) standards, national laws, and international obligations. Using a doctrinal research approach, the study inventories and interprets legal materials, systematizes themes, and evaluates compliance and gaps. The analysis finds widespread gaps at international, national, and delegated levels of oversight that undermine airworthiness and safety, highlighting the interaction among regulatory frameworks, corporate practices, and liability regimes. From these findings, the study proposes policy directions to strengthen independent oversight, minimize conflicts of interest in certification processes, and enhance overall aviation accountability. For Indonesia, in particular, the results call for a targeted reform agenda: harmonization of national regulations with ICAO Civil Aviation Safety Regulation (CASRs), robust surveillance and enforcement mechanisms, and greater transparency in airworthiness actions. Implementing these measures would advance Indonesia’s capacity to ensure safe, reliable air travel and contribute to global aviation safety.